The Correlation Between Fine Needle Aspiration Cytology and Histopathology of Head and Neck Lesions in Kathmandu University Hospital - Rajbhandari, M; Dhakal, P; Shrestha, S; Sharma, S; Shrestha, S; Pokharel, M; Shrestha, I; Shrestha, B; Makaju, R (Kathmandu University Medical Journal, 2015)
Background Fine needle aspiration cytology (FNAC) with it’s minimally invasiveness has been a well accepted procedure in the initial diagnosis of various swellings. With time and experience high sensitivity and specificity of FNAC over conventional open biopsy has lead to the wide acceptance of this procedure.Objective To evaluate the utility of aspiration cytology as a first-line diagnostic tool in palpable head and neck masses and correlate with histologic results for evaluating diagnostic accuracy.Methods A hospital based prospective, comparative study was conducted among patients with various swellings at Head and Neck regions in the Department of Pathology, Dhulikhel Hospital between July 2011 to June 2012. FNAC were done from the palpable masses of head and neck regions and were compared with biopsy findings of the same lesions. Data entry and analysis performed using SPSS version 16. The sensitivity, specificity and accuracy rates were calculated.Results A total 64 patients were subjected to both FNAC and histopathological examination (HPE). Total 39 (61 %) were females and 25 (39 %) were males with M: F ratio of 1:1.6. The age group ranged from 9 to 80 years. Twenty five percent of patients were in the age group below 20 years. The highest number of cases included lymph nodes 29 (45%) followed by thyroid 24(37.5 %), salivary glands 10(16%) and 1 case (1.6%) was a soft tissue swelling over the occipital region. Highest sensitivity, specificity and accuracy rate for diagnosis by FNAC were observed in thyroid. The overall sensitivity and specificity of FNAC were 86% and 97% respectively in determining the various pathologies. The overall accuracy of FNAC in present study was 87.4%.Conclusion FNAC is a minimally invasive first line investigation with a high sensitivity and specificity for the diagnosis of various head and neck lesionsKathmandu Univ Med J 2013; 11(4): 296-299